Difficult situations in the work of nurses in selected hospital wards - Motyka, Marek; Lickiewicz, Jakub (Nursing in the 21st Century, 2013)
DIFFICULT SITUATIONS IN THE WORK OF NURSES IN SELECTED HOSPITAL WARDS Stress and difficult situations are an integral part of nursing work. The aim of this study was therefore to identify the main sources of stress that occurs in nursing and to verify if they are different depending on the department in which nurses are employed. The research included staff working in internal medicine, psychiatric and neurological surgery wards. A projective technique and interview were used as the research methods. The research showed differences in the types of difficult situations, which nurses faced in their work performed in different wards and differences in feeling emotions in various situations due to relations to patients and their families.